Efektivitas Rancangan Media Pembelajaran Berbasis Teknologi Informasi dalam Meningkatkan Literasi Numerasi di SMP Negeri 11 Gorontalo - Bito, Nursiya; Hadjaratie, Lillyan; Katili, Nancy; Hasdiana, Hasdiana; Badu, Syamsu Qamar; Hulukati, Evi; Djafrie, Novianty (Department of Mathematics, Universitas Negeri Gorontalo, 2023)
The application of technology can make it easier to understand and solve mathematical problems. Therefore, there is a need to integrate technology in mathematics learning. Technology can act as a learning medium. This research aims to determine the effectiveness of using information technology-based learning media in mathematics learning to improve numeracy literacy in Class VIII of SMP Negeri 11 Gorontalo. The method used is descriptive qualitative. The indicators used to determine the effectiveness of learning are the teacher's ability to manage learning, student learning activities, and student numeracy literacy test results. Based on the research results, it was found that the teacher's ability to manage student learning and activities was categorized as effective, and the results of the students' numeracy literacy tests were classically complete. Thus, information technology-based learning is effective in increasing students' numeracy literacy at SMP Negeri 11 Gorontalo.